Menggagas Reformasi Pendidikan Islam: Telaah Filosofis Paradigmatik - Ismail Thoib (Universitas Islam Negeri Mataram, 2007)
Discourse of religious education reform highlights at least two important pillars, philosophical and theoretical framework. Both frameworks are convinced as strong foundation of religious education development under rational-empirical principles of world society development. A lot of violence on the name of religion occur in the world and, to some extent, are found as religious education failure because of its exclusive learning model, which drive students far from their real multidimensional life problems. Responding to such situation religious education need to reform itself properly. In the context of Islamic education reform, we need to develop a kind of paradigmatically philosophical logics of Islamic education. There are two steps to take: forming philosophically fundamental framework of education, and developing rationally and empirically principles of educational practices in accordance with its structural and cultural context. It implies that the logics of Islamic education philosophically deal with both profane and sacred dimension of human life.